A study on demotivating factors in English reading comprehension lessons of the 10th - form students at My Duc A high school, Hanoi = Nghiên cứu các yếu tố gây mất hứng thú trong giờ học đọc hiểu tiếng của học sinh lớp 10 Trường THPT Mỹ Đ - Nguyễn, Thị Phương (University of Languages and International Studies, 2017)
45 p. + CD-ROM